Improving Student Learning Outcomes and Creativity through Project-Based Differentiated Learning - Ruspeniati Ruspeniati; Sudarmiani Sudarmiani (STAI MA'ARIF MAGETAN, INDONESIA, 2025)
This research examines the competence of social studies teachers in developing learning tools at public junior high schools in Madiun City. Using a qualitative descriptive approach, the research was conducted at 14 SMP Negeri Kota Madiun during the 2024/2025 academic year. The research focuses on three main aspects: ability to develop teaching modules, learning materials, and assessment designs according to the demands of the Merdeka Curriculum. The results show that social studies teachers have adequate capability in developing learning tools. In terms of teaching modules, teachers have developed modules based on Learning Objectives Pathways (ATP) with approaches focused on students' interests and talents. Regarding learning materials, teachers have developed contextual materials that address social issues in students' environments, using diverse teaching strategies and methods. In assessment aspects, teachers have implemented formative and summative assessments, conducting continuous and comprehensive evaluations. The main challenges include difficulties in formulating measurable learning objectives, developing contextual materials, and designing comprehensive assessments. Supporting factors for successful implementation include teacher creativity, student motivation, and school support, while the inhibiting factors include lack of understanding about the Merdeka Curriculum, limited training opportunities, and minimal supporting facilities.